Aplikasi Pengelolaan Data Barang pada Apotik Kaka Farma: Studi Kasus: Kaka Farma Jl. Cigantri Mas kec.Bojongsoang kab. Bandung - Muhammad Gibran; Novita Anggraini (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The Kaka Farma Pharmacy is a pharmacy that operates in the field of selling medicines. The system currently running at the Kaka Farma Pharmacy uses a manual system so that it often experiences problems with calculations, validating information, slow transactions, and difficulty making reports. This research aims to analyze sales transactions at the Kaka Farma Pharmacy which relate to incoming and outgoing goods. After knowing the problems and feasibility, then designing a more effective proposed system that can be implemented with a MySQL database, then building a website-based product data management application for Kaka Farma pharmacies using PHP language. The results of this research are in the form of an item data management application at the Kaka Farma pharmacy to handle data input and then process it to produce output in the form of report data that can be evaluated.